Examining the Scale, Impacts of, and Response to, Illegal Logging in the Global Context - Cao Ngoc Anh, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Globally, illegal logging has been one of the most profitable and fastest-growing types of transnational organized and environmental crime. Its black market has created a large domestic public outcry and generated a great deal of detrimental impacts on economic, social, environmental, and political security. However, illegal logging has been frequently overlooked by researchers, leading to limited understanding about the crime and the harmful consequences. Against this backdrop, by employing the secondary analysis method, this paper is designed to evaluate the scale of illegal logging, its diverse impacts, and international efforts to deal with this type of crime. It is found in this study that illegal logging remains extensive and increasingly sophisticated, transnational and organized across the world demonstrated by very high illicit profits, timber volumes and destroyed forest areas with inseparable links to other examples of major criminality, especially corruption. Although the crime generates abundant and detrimental economic, social, environmental, and political consequences, on the ground, the impact of global efforts to address the crime is dwarfed by its scale.Received 24th March 2020; Revised 17thAugust 2020; Accepted 26th September 2020